Agglomerated Ag–Pd catalyst with performance for hydrogen generation from formic acid at room temperature. (12th January 2016) - Liu, Jun; Lan, Lixin; Li, Rong; Liu, Xuanyan; Wu, Chao
Abstract: We report a simple method for the fabrication of agglomerated Ag–Pd nanocomposites by the addition of NaBH4 . The agglomerated Ag–Pd nanocomposites are characterized SEM, TEM, XRD and XPS measurements. The prepared Ag–Pd nanocomposites exhibited catalytic activity in hydrogen generation from decomposition of formic acid at room temperature (∼25 °C). Herein, the present Ag–Pd catalysts possess the new type of agglomerated structure against to dispersion, which make them easily separated from the reaction system. It is convenient for operator to cease catalytic reaction at any moment. Moreover, the resulting Ag–Pd catalysts can be easily reactivated simply by drying after water cleaning for reuse, which saved the cost of catalysts. Among them, Ag1 Pd3 sample showed nice performance of recycle test and long lifetime for the decomposition of formic acid at room temperature. We hope that this work opens a new avenue to develop solid catalysts for hydrogen production from formic acid decomposition in solution. Graphical abstract: One-step reduction method was explored to prepare agglomerated Ag–Pd catalyst with catalytic activity for the production of hydrogen from formic acid decomposition at room temperature. High light: Agglomerated Ag–Pd alloy catalyst has been prepared by a chemical reduction method. The Ag–Pd catalyst show catalytic activity for formic acid decomposition. The catalytic reactions were performed at room temperature without heating. The present Ag–Pd catalysts were easily separated from the reaction system. The Ag–Pd catalysts can be easily reactivated for reuse.